2022
DOI: 10.1590/01047760202228013055
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of remaining populations of paratecoma peroba, an endangered and endemic species of the atlantic forest

Abstract: Background:The objective of this study was the genetic characterization of remaining populations of the species Paratecoma peroba occurring in fragments of the Atlantic Forest, by estimating parameters of diversity and genetic structure. The study was carried out in two forest fragments, the Atlantic Forest Environmental Education Pole (area 1) and the Pacotuba National Forest (area 2), where 93 adult trees were identified.Results: Ten Inter Simple Sequence Repeats (ISSR) primers were used in genotyping, obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Therefore, other comparisons can be extended to populations of forest species located in sampling areas evaluated in this study or that are close and that have been genetically characterized via ISSR markers, such as for Dalbergia nigra where low genetic diversity was identified in Area 2 (Silva Júnior et al, 2022), and Paratecoma peroba where the study also identified low genetic diversity in two Conservation Units close to Areas 2 and 3 (França et al, 2022).…”
Section: Genetic Diversity and Dissimilaritymentioning
confidence: 99%
“…Therefore, other comparisons can be extended to populations of forest species located in sampling areas evaluated in this study or that are close and that have been genetically characterized via ISSR markers, such as for Dalbergia nigra where low genetic diversity was identified in Area 2 (Silva Júnior et al, 2022), and Paratecoma peroba where the study also identified low genetic diversity in two Conservation Units close to Areas 2 and 3 (França et al, 2022).…”
Section: Genetic Diversity and Dissimilaritymentioning
confidence: 99%